Chester Barkingham Saves the Country - Falatko, Julie; Byrne, Eva; Simon and Schuster, Inc. Childrens Publishing Division (New York : Simon & Schuster Books for Young Readers, 2024)
A White House dog teaches lawmakers how to be better humans in this hilarious picture book told in presidential memos! Good dog Chester Barkingham moves into his forever home--the White House!--when hes adopted by the presidents daughter. The president sends memos to let everybody know about Chester joining the staff and, soon enough, the trouble he gets into. The president has other things to worry about, though. Congress cant seem to get along, and bills are getting stalled as both sides argue and debate. Chester knows just what to do about the deadlock...if anybody would listen to him. When Chester starts sending memos of his own, Capitol Hill turns upside down--which may be just what everybody needs.--
Keywords: Dogs -- Juvenile fiction; Pet adoption -- Juvenile fiction; Presidents -- Juvenile fiction; United States -- Politics and government; Juvenile fiction; Animal fiction; Picture books